Who’s Teaching Which Languages Online? A Report Based on National Surveys - Murphy-Judy, Kathryn A.; Johnshoy, Marlene (IALLT Journal of Language Learning Technologies, 2017)
This paper describes findings from recent national surveys on online language education (OLE) within a broader context of national surveys of post-secondary online education and  world language enrollments. The surveys discussed and compared are the 2012 CARLA Survey by Johnshoy and BOLDD Surveys by Murphy-Judy (2014 & 2015). The findings reported here include: types and sizes of institutions; demographics of the teaching corps (CARLA data only); and, the mix of languages and levels. This work aims to provide useful information on online language education as it emerges as an important field in world language teaching and learning in the 21st century.